Enterprise networking multilayer switching and applications - Theoharakis, Vasilis 1967-; Serpanos, Dimitrios Nikolaou (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2002)
Primarily targeted toward the network or MIS manager who wants to stay abreast of the latest networking technology, this title offers up to date information relevant for the design of modern corporate networks and for the evaluation of new networking equipment. The book describes the architectures and standards of switching across the various protocol layers and will also address issues such as multicast quality of service, high-availability and network policies that are requirements of modern switched networks
Includes bibliographical references and index. - Title from PDF t.p. (viewed on May 25, 2010)
Keywords: Business enterprises -- Computer networks; Local area networks (Computer networks); Wide area networks (Computer networks)